2023
DOI: 10.1021/jacsau.3c00418
|View full text |Cite
|
Sign up to set email alerts
|

How Amorphous Nanomaterials Enhanced Electrocatalytic, SERS, and Mechanical Properties

Jianxin Kang,
Fengshi Li,
Ziyan Xu
et al.

Abstract: There is ever-growing research interest in nanomaterials because of the unique properties that emerge on the nanometer scale. While crystalline nanomaterials have received a surge of attention for exhibiting state-of-the-art properties in various fields, their amorphous counterparts have also attracted attention in recent years owing to their unique structural features that crystalline materials lack. In short, amorphous nanomaterials only have short-range order at the atomic scale, and their atomic packing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…Nevertheless, the samples obtained were amorphous, in this context there were designed transducers (such as nano wires) based on titanium dioxide, silicon, ferric, cooper, gold and silver. Even though, the samples are amorphous, it does not mean that cannot be useful [15,16], these samples are useful as clusters with good performance in the electromagnetic absorbance (for the wireless sensors designed in this task).…”
Section: Experimental Analysismentioning
confidence: 99%
“…Nevertheless, the samples obtained were amorphous, in this context there were designed transducers (such as nano wires) based on titanium dioxide, silicon, ferric, cooper, gold and silver. Even though, the samples are amorphous, it does not mean that cannot be useful [15,16], these samples are useful as clusters with good performance in the electromagnetic absorbance (for the wireless sensors designed in this task).…”
Section: Experimental Analysismentioning
confidence: 99%
“…With regard to semiconductor substrates, the SERS enhancement mainly arises from the enhanced chemical bond vibration of molecules caused by the charge transfer between substrates and molecules. Currently, a large number of literature studies have confirmed that the amorphization of SERS substrates is able to conspicuously increase the excited electrons near the Fermi level, thereby developing the chemical enhancement effect of semiconductor materials on probe molecules. Hence, forming a uniform amorphous layer on the surface of crystalline MXene nanosheets may be an efficient method to further improve the SERS detection sensitivity. In conclusion, the combination of 3D assembling and amorphizing MXene nanosheets is expected to synergistically improve the SERS performance of MXenes from three aspects of physical enrichment, CM, and EM and thus propose a universal experimental strategy that can conspicuously optimize the SERS sensitivity of MXenes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its amorphous carbon structure, reduced graphene oxide (rGO) can form an even broader variety of structures (e.g., wrinkles, interlayer distance, thickness, and porosity) compared to other nanomaterials. [7] For example, wrinkles in rGO-based structures create digitated tunnels that act as individual nanoelectrodes [6a] . This not only increases the total geometric surface area, but also improves electroconductivity by electron and mass transfer kinetics [8] , and sensitivity by increasing the loading capacity of receptors.…”
Section: Introductionmentioning
confidence: 99%